THE IMPACT OF ENTREPRENEURIAL NETWORKING ON SUSTAINABLE GROWTH OF CULINARY MSMES: MEDIATING ROLE OF INNOVATION - I Made Bagus Riawan; Louis Utama (Graduate Program of Universitas Tarumanagara, 2026)
This study aims to examine the influence of entrepreneurial networking on sustainable growth through innovation as a mediating variable among culinary MSMEs in Depok, Indonesia The study adopts a quantitative research design, the sample in this study consists of 180 respondents who are culinary MSME owners operating in CFD Depok and Bazar Pagi Depok, selected using a purposive sampling technique with criteria of having operated for at least six months. Data were collected through an online and offline questionnaire survey and analyzed statistically using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with SmartPLS v4 software. The results show that Network Social Capital (NSC) has a significant positive effect on Innovation (I) and Sustainable Growth (SG), Furthermore, Network Isomorphism (NI) also demonstrates a significant positive influence on Innovation (I) and Sustainable Growth (SG). In addition, Innovation (I) has been proven to have a significant positive effect on Sustainable Growth (SG), Moreover, Innovation also acts as a mediating variable that bridges the relationship between entrepreneurial networking (NSC and NI) and sustainable growth